Development of e-module learning media for finishing clothing edges in basic sewing techniques for students at SMK N 2 Sewon Yogyakarta - Armelia Putri, Wina; Andayani, Sri Wahyu; Kartikasari, Enggar (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to 1) develop learning media e-module clothing edge finish; 2) knowing the feasibility of learning media by material experts and media experts; 3) knowing students' responses to learning media. This research is a research and development or Research and Development (R&D) with a 4D (Four-D) development model consisting of the stages of define, design, development , disseminate. The learning media developed is in the form of flipbook-based learning e-modules. The subject of this study is a grade X student of Fashion Design of SMK Negeri 2 Sewon for the 2023/2024 school year. The object of this study is the clothing edge finishing e-module. The instruments used are observations and questionnaires addressed to material experts, media experts and students. Data analysis techniques use quantitative descriptive analysis. The results showed that 1) The development of learning media resulted in e-module completion of clothing edges which was carried out through 4 stages of development, namely the stages of define, design , development, disseminate, 2) development of learning media e-module completion of clothing edges suitable for use as learning media and learning resources based on the results of feasibility tests by material experts and media experts with a percentage of 100% (feasible), 3) student responses to the e-module learning media Clothing Edge Completion was declared to be used as a learning medium and learning resource based on the results of small-scale product trials with 8 respondents getting a percentage of 88.75% (strongly Agree) and the results of limited-scale product trials with 36 respondents getting a percentage of 88.92% (strongly Agree). This shows that the learning media e-module finishing the edge of clothing can be used as a learning medium in the teaching and learning process. Keywords: e-module, clothing edge solution, sewing base technique